Karakteristik Komite Audit Memoderasi Pengaruh Penerbitan Opini Going Concern Pada Pergantian Auditor - Ismaya Sukrapratiwi, Ida Ayu; Yenni Latrini, Made (E-Jurnal Akuntansi, 2015)
Auditors might be switched because of going concern opinion. The audit committee is one of the corporate governance mechanism that is expected to become an independent party that is able to reduce the tendency of the change of auditor. The purpose of this study was to examine the impact of the characteristics of the audit committee as a moderating impact on the going concern opinion publishing auditor turnover, and the relationship of publishing going concern opinion by the auditor turnover. This study was conducted on 136 listed manufacturing companies in BEI from 2010 - 2013, the sample used is 41 companies using purposive sampling. The analysis technique used is logistic regression analysis and Moderated Regression Analysis. The results of this study indicate that the issuance of going concern opinion has no effect on the change of auditors. Characteristics of an audit committee comprised of accounting and financial competency skills, and activities of the audit committee is not able to moderate the effect of the issuance of going concern opinion at the turn of the auditor.
Keywords: going concern opinion, audit committee, audit committee activities, auditor switching